Mediating effects of insulin resistance on lipid metabolism with elevated paraben exposure in the general Taiwan population - Huang, Po-Chin; Chen, Hsin-Chang; Huang, Han-Bin; Lin, Yu-Lung; Chang, Wan-Ting; Leung, Shih-Hao; Chen, Hsi; Chang, Jung-Wei (Frontiers in Public Health, 2025)
IntroductionParabens are commonly used to prevent bacteria from growing in cosmetics and foodstuffs. Parabens have been reported to influence hormone regulation, potentially leading to metabolic anomalies, including insulin resistance and obesity. However, there is a paucity of knowledge regarding the relationship between urinary paraben levels and lipid metabolism in the general Taiwanese population. Therefore, the objective of this study was to determine whether the mediating role of insulin resistance exists between paraben exposure and lipid metabolism.MethodsWe selected the data of 264 adult participants from a representative survey in five major Taiwan area in 2013. UPLC tandem mass spectrometry was used to examine four urine parabens: methyl- (MeP), ethyl- (EtP), propyl- (PrP) and butyl- (BuP). Blood samples were analyzed for concentrations of glucose and lipid metabolic indices using the DxI 800 immunoassay analyzer and immunoradiometric assay kit. The relationship between urinary paraben levels and metabolism indices were evaluated through a multiple linear regression analysis. Finally, a mediation analysis was employed to understand the underlying mechanism by which paraben exposure influences lipid metabolism through insulin resistance.ResultsThe significant positive association between MeP exposure and Castelli risk index I (CRI-I; β = 0.05, p = 0.049) was found, and also exhibited the similar associations between EtP exposure and low-density lipoprotein cholesterol (β = 0.10, p = 0.001), total cholesterol (β = 0.06, p = 0.003), and non-HDL cholesterol (NHC; β = 0.08, p = 0.005). EtP exhibited a significant positive association with triglyceride BMI (TyG-BMI; β = 0.02, p = 0.040). Additionally, TyG-BMI was positively associated with CRI-I (β = 0.98, p < 0.001), CRI-II (β = 1.03, p < 0.001) and NHC (β = 0.63, p < 0.001). Moreover, insulin resistance served as mediators for the effects of EtP exposure on lipid metabolism indices.DiscussionThe results indicate that changes in insulin resistance mediated the relationship between urinary paraben and lipid metabolism. Large-scale epidemiological and animal studies are warranted to identify biological mechanisms underlying validate these relationships.